Direct amide synthesis via Ni-mediated aminocarbonylation of arylboronic acids with CO and nitroarenes. Issue 91 (28th October 2019) - Shen, Ni; Cheung, Chi Wai; Ma, Jun-An
Abstract : Ni metal-mediated aminocarbonylation based on readily available arylboronic acids, nitroarenes, and carbon monoxide was achieved to prepare a variety of aryl amides. Abstract : Herein we describe an alternative and unconventional approach of an aminocarbonylation reaction to access aryl amides from readily available and low-cost arylboronic acids and nitroarenes. Nickel metal can serve as both reductant and catalyst in this direct aminocarbonylation. This protocol exhibits a good functional group compatibility and allows a variety of aryl amides to be synthesized, including several drug-like molecules.